Using Publicly Available Data to Understand the Opioid Overdose Epidemic: Geospatial Distribution of Discarded Needles in Boston, Massachusetts - Bearnot, Benjamin (Am J Public Health, 2018)
Objectives. To use publicly available, crowdsourced data to understand geospatial trends in discarded needles. Methods. We completed multiple geospatial analyses of discarded needles reported through the Boston, Massachusetts, 311 service request system. Results. Between May 2015 and August 2017, 4763 discarded needles were reported. The highest concentration of needles were reported in census block groups in the South End and Roxbury neighborhoods. Cumulatively, 78.3% of the needles were reported within 1 kilometer of methadone clinics, safe needle deposit sites, homeless shelters, or hospitals. Conclusions. Publicly reported data can help identify hot spots of discarded needles and examine indicators of spatial association. In Boston, the number of discarded needles being reported is rising, with the highest density of needles found in 2 central neighborhoods with several outlying hot spots. Most needles were found near areas associated with social stress and substance use disorder. Public Health Implications. This analysis represents a novel way of leveraging publicly available information to target community responses to the opioid epidemic. Identifying hot spots of discarded needles may enable public health organizations to target future efforts to encourage safer needle disposal practices and reduce public injection drug use.